O3 Mainstreaming qualitative longitudinal research and re-thinking causality in a global health context. (20th March 2019) - Webster, Jayne; Neale, Bren; Gooding, Kate; Hill, Jenny
Abstract : As a rich and flexible methodology for discerning dynamic processes, Qualitative Longitudinal (QL) research follows the same individuals or small collectives prospectively, in 'real' time, as lives unfold. It has the power to mirror real world processes, to investigate how and why changes occur, and to discern the mechanisms that shape these processes (Neale 2018). This capacity is vital where people are required or encouraged to change their practices or otherwise adapt to changing circumstances or environments over time. In recent years this approach has been used increasingly in health services research. 1, 2 However, there have been few attempts in this field to document its use or explore its theoretical underpinnings. This presentation will outline the design and development of an ambitious programme of QL research, the Health Utilisation Dynamics Study, directed by PATH. This is a qualitative 'add on' to a large-scale evaluation of the Malaria Vaccine Implementation Programme in Ghana, Kenya and Malawi. QL enquiry is uniquely placed to investigate health and illness biographies, changing health policies, the delivery, uptake and sustainability of new treatments, and to produce dynamic case studies of local health care systems. These are central themes in this study. In particular, we will explore innovative ways to discern causal mechanisms across the micro-macro plane. Our aim is to reflect the dynamic, open-ended and fluid nature of social actions, reactions, effects and counter effects in complex systems of change. References: Calman L, Brunton L and Molassiotis A. Developing longitudinal qualitative designs: lessons learned and recommendations for health services research. BMC medical research methodology 2013;13:14. Grossoehme D and Lipstein E. Analyzing longitudinal qualitative data: the application of trajectory and recurrent cross-sectional approaches. BMC research notes 2016;9:136.